Sistem Supervisory Control and Data Acquisition pada Generator Set - Yayuk Suprihartini; Panji Muhammad Putra; Bachrul Huda (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
Generator set is a device that can convert mechanical energy into electrical energy. In Addition, generators are used to back up the electricity supply when the main power source (PLN) goes out one of the supporting factors for students to know the implementation of the output data generated by the generator set, we need a special system that can monitor the generator and can also control it centrally. To monitor and controlthe system, a system called SCADA is needed. This design can monitor the work system on the generator and control the the load to be supplied by the generator. This design uses Arduino hardware as a base and display using Visual Studio 2019.